2008
DOI: 10.7124/bc.0007c4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient gene delivery into mammalian cells by baculovirus vector in vitro

Abstract: The recombinant baculovirus vector with EGFP reporter gene under the control of strong CAG promoter cassette was used for transduction of normal (HEK293) and tumor (HeLa) human cell lines. Dependence of transduction efficiency on the virus dose, time of virus incubation, temperature and cell type is shown. Transient reporter gene expression gradually diminished and was detected in single cells on the 15 th day after transduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…It is known that BVs provide transient expression of transgenes in non-permissive mammalian cells in the absence of viral replication and a gradual loss of viral DNA upon cell division. As was shown earlier, the expression of GFP reporter protein may last for 30 days gradually decreasing, but stored in some single cells [28,30]. Using q-PCR, we showed that Ifnβ was expressed at a high level for 120 hours, substantially equal to that observed immediately after transduction (Fig.…”
Section: Analysis Of Ifnβ Expression In C57fb Cells Transduced With supporting
confidence: 72%
See 1 more Smart Citation
“…It is known that BVs provide transient expression of transgenes in non-permissive mammalian cells in the absence of viral replication and a gradual loss of viral DNA upon cell division. As was shown earlier, the expression of GFP reporter protein may last for 30 days gradually decreasing, but stored in some single cells [28,30]. Using q-PCR, we showed that Ifnβ was expressed at a high level for 120 hours, substantially equal to that observed immediately after transduction (Fig.…”
Section: Analysis Of Ifnβ Expression In C57fb Cells Transduced With supporting
confidence: 72%
“…The virus was concentrated by centrifugation at 100000 g. The titer of viruses preparations was 2-4×10 8 pfu/ml. Transduction was performed as desribed previously [28]. C57Fb cells were incubated with recombinant BVs at a concentration of 200 moi (multiplicity of infection = pfu per cell) for 4 hours at 28 °C in phosphate buffered saline (PBS), followed by addition of 1.5 ml DMEM medium and culturing for 16 hours at 37 °C.…”
Section: Baculovirus Vectors (Bvs) and Mef Transductionmentioning
confidence: 99%
“…Plasmid pFastBac was used as a donor plasmid. According to the protocols, recombinant baculoviruses AcGFP were obtained under the CMV virus gene promoter for expression in mammalian cells with the Green fluorescent protein (GFP) gene embedded in the cassette under the CV40 promoter [20,21]. Recom bi nant baculovirus AcGFP-TAGLN contained both the TAGLN and the GFP gene in the cassette.…”
Section: Construction Of Recombinant Baculovirusesmentioning
confidence: 99%
“…A monolayer culture of Sf21 insect cells was grown in TC-100 medium (Sigma) with the addition of 10 % FBS at 28 °C. Transfection of cells by recombinant baculoviruses was carried out according to the standard procedures [21].…”
Section: Construction Of Recombinant Baculovirusesmentioning
confidence: 99%
See 1 more Smart Citation